Handling compressed gas cylinders - Weber, Charles M.; The MARCOM Group, Ltd. (Boothwyn, PA : The MARCOM Group, Ltd., 1993)
This program explains the four ways to compress gases, hazards of compressed gases, proper storage procedures, marking and labels, handling cylinders safety, connections and fittings and leak detection
Title from title screen
Executive producer, Donald L. Leonard
Keywords: Gases, Compressed -- Safety measures; Gas cylinders -- Inspection; Materials handling